Factors Affecting the Technological Entrepreneurship Development in Sirajganj, Bangladesh (Global Journal of Management and Business Research, 2021)
The study aims to identify various factors leading to the development of technological entrepreneurship as it is a new concept of transforming the research potential and abilities of scientific organizations based on the context of new products and services. This study has attempted to recognize different circumstantial facts of technological entrepreneurship from regional consideration. This study is related to the factors affecting entrepreneurship development issues from the entrepreneurship development model in Bangladesh, particularly in Sirajganj. The primary data has been collected through a well-set questionnaire on the other hand secondary data collection formulated from different reliable sources. After transformation, it has been mechanized to meet the study#x2019;s objectives by using SPSS version 23. From both the qualitative and quantitative reasoning, the researcher believes ethical concerns are needed to ensure validity. Data analysis exhibits factor tests and reliability of statistics categorically to validate the hypotheses. These types of businesses are growing in popularity and contributing to Bangladesh#x2019;s overall economy due to globalization and digitalization. Entrepreneurs#x2019; regional consideration demands some incentives and initiatives from the government, such as financial incentives and favorable economic policy initiatives to speed up the country#x2019;s socioeconomic development. There is a linkage between digitalization and entrepreneurship development. People#x2019;s positive attitudes toward regional economic development create new opportunities for entrepreneurs.
Keywords: technological entrepreneurship; factors; development; digitalization